Pengembangan Digitalisasi Arsip pada Bidang Pendidikan di Indonesia : Tinjauan Pustaka Sistematis - Aminullah, Andi Muhammad; Riscal, Detty Agustin; Sahbany, Sri (Prodi Perpustakaan dan Sains Informasi, 2023)
This study aims to determine the development of archive digitization in the field of education in Indonesia. The method used in this study is a systematic literature review which provides output to existing data, as well as the elaboration of a finding so that it can be used as an example for research studies in compiling or making a clear discussion of the content of the problem to be studied.The author looks for data or literature material from journals or articles and also references from books so that it can be used as a strong foundation in the content or discussion. The results of the research found are as follows: 1) The implementation of archive digitization management in the field of education is always directed to achieve the success of organizational goals effectively and efficiently. One of the factors that can support success in achieving goals is order in the field of administration. 2) the competence of archive managers in the field of education, human resources who really understand the procedures for managing records in the field of education are good and correct, then special assistance is needed in terms of records management, one of which is providing training on digitizing archives based on 8 National Education Standards. 3) Obstacles in the development of archive digitization in the field of education, still encounter many obstacles, both technical, financial, and policy. Nevertheless, the enthusiasm to develop digitalization in Indonesia has never diminished.